Expression of Leptin Receptor and Effects of Leptin on Papillary Thyroid Carcinoma Cells. (14th February 2019) - Celano, Marilena; Maggisano, Valentina; Lepore, Saverio Massimo; Sponziello, Marialuisa; Pecce, Valeria; Verrienti, Antonella; Durante, Cosimo; Maranghi, Marianna; Lucia, Piernatale; Bulotta, Stefania; Damante, Giuseppe; Russo, Diego
Abstract : Background . Obesity has been hypothesized to contribute to the aggressiveness of thyroid cancer through the production of abnormal levels of serum adipokines. Leptin receptor (OB-R) expression has also been documented in papillary thyroid cancer (PTC). Aim . In this translational study, we analyzed in vitro the effects of leptin on the growth and migration of thyroid cancer cells (TPC-1 and K1), the molecular mechanisms underlying leptin's action, and the influence of prolonged leptin exposure on cell response to a protein kinase inhibitor lenvatinib. The expression levels of OB-R mRNA and protein were also investigated in vivo in a series of aggressive PTCs divided into two groups based on the presence of the BRAF mutation. Results . In TPC-1 and K1 cells, prolonged treatment with leptin (500 ng/ml for 96 h) resulted in a mild increase in the proliferation (about 20% over control only in K1 cells, p < 0.05 ) and in the migration of both cancer cell lines. Immunoblot analysis revealed a slight increase in the phosphorylation of AKT, but no effect on β -catenin and phospho-ERK expressions. The inhibitory effects of lenvatinib on the viability of both cell lines were not influenced by the leptin treatment . OB-R transcript (in fresh tissues) and proteins (in formalin-fixed and paraffin-embedded specimens) were expressed in all PTC tissues examined, with no significant differences between BRAF- mutated and BRAF -wild-type tumors. Conclusions . These results demonstrate leptin's role in mildly increasing the aggressive phenotype of PTC cells but without influencing the action of lenvatinib. Further studies will clarify whether it is possible to target OB-R, expressed in all aggressive PTCs, as an adjuvant treatment approach for these malignancies.